Olympic debrief - Dick, F. (IFAC, 2013)
Der Autor präsentierte in einer ppt auf dem International Festival of Athletics Coaching am 25.-27. Oktober 2013 in Glasgow/Scotland eine Nachbetrachtung der Resultate in der Leichtathletik bei den Olympischen Sommerspielen 2012. Er geht u. a. auf Fragen ein wie Short Term Review - Individual Debrief: 1.What is the performance target? 2.What tasks are required to achieve the performance? 3.What actions are carried out to complete the task? 4.What is the current performance? 5.If it exceeds the target, recognise, appreciate and improve farther. 6.If it is below target, diagnose problems and correct. 7.What is the revised performance target? Medium Term Reviews: 1.What are the performance components relative to the person`s role? (Key Performance Determinants - KPD`s). 2.What are the agreed standards for those components re the person`s performance target? 3.What are the delivered/present standards in these components 4.When these match or are better than those agreed, recognize, appreciate and improve. 5.If not, diagnose problems and correct them. 6.What are the revised performance component standards? Schwerpunktthemen sind außerdem: - Results - intended and actual. - Performance under pressure of athletes and teams. - Professional competence of all staff coaching, management, administration and performance support. - Effectiveness of athlete and team staff in preparation planning. - Effectiveness of overall campaign strategy/current year plan/applied game plan. - Leverage of high performance intelligence and resources, e.g. systems and technology. - Quality of chief coach decision making and judgment calls. - Comparison of Points per Top 20 Nations at the Games 2004, 2008, 2012 - Performance overview (Men/women) in the sprint, hurdles, relays, throws, endurance disciplines, jumps and decathlon/heptatlon - Age Distribution among the finalists and the medalists. - Results at the Junior World Championships, - Medals or Season`s Best (or better) during London 2012 and Medals or Season`s Best in the Athlete`s Final Performance in the Competition. Abschließend geht der Autor der Frage nach: Does Coach Education and Development prepare coaches for this task? und gibt folgende Empfehlungen: 1.National Coaching & Performance Leadership. High performance: - Coach Development & management - Athlete Development Junior - Peak Performance - Performance Directors - Performance Structures 2.High Priority - head Coach Junior Program 3.Athlete Development Pathway Review - Junior - Peak Performance - Delivering "on the day" 4.Junior - Peak Performance years attrition - why? 5.Replace IAAF World Youth with U/23 6.Coach Education Program review - Performance - Delivering on the day 7.Coaching and performance related roles and responsibilities defined 8.European IAAF Junior Medalists and Coaches target for essential support and development 9.Sprints & Hurdles European Priority Coaching & Performance Program. Track endurance to follow 10.Endurance athlete development for competitive races rather than paced races 11.Long Jump & High Jump performance & coaching review to raise global standards